The domestic politics of international prestige - Brancati, D. (2018)
Although international prestige is a key component of international politics, not all states seek it to the same extent as others. States, I argue, seek international prestige in order to build domestic political support. The extent to which depends on how much of the population states rely on for authority to govern and whether they do so through open and competitive elections. By shifting the focus from the dynamics between states to those within states, and by testing this argument statistically using a novel measure of prestige-seeking - Olympic success, this research adds a new dimension to extant knowledge on international prestige. The statistical results show, consistent with this argument, that authoritarian regimes that rely on a large segment of their population for authority - party and personalist regimes - are more successful at the Olympics than those that rely on a small one - military regimes and monarchies, as well as democracies.